Whole mount immunofluorescence analysis of placentas from normotensive versus preeclamptic pregnancies. Issue 11 (November 2015) - Zozzaro-Smith, P.E.; Bushway, M.E.; Gerber, S.A.; Hebert, D.; Pressman, E.K.; Lord, E.M.; Miller, R.K.; Murphy, S.P.
Abstract: Introduction: Defects in placental angiogenesis and spiral artery remodeling have been proposed to play essential roles in the development of preeclampsia. However, the specific molecular mechanism(s) responsible for aberrant placental angiogenesis in preeclampsia are incompletely understood. The vascular endothelial growth factor receptors (VEGFR1, R2, R3) and STAT3 have critical functions in normal blood vessel development, but their potential roles in preeclampsia are currently unclear. In this study, we utilized a novel whole mount immunofluorescence (WMIF) method to compare expression of VEGFR1, R2, R3 and activated, phosphorylated STAT3 (pSTAT3) in placentas of preeclamptic (PE) versus normotensive (NT) pregnancies. Methods: Placental biopsies collected from NT and PE pregnant women were fixed and stained with fluorochrome-conjugated antibodies to identify specific cell populations as follows: CD31 for blood vessel endothelial cells, cytokeratin-7 for trophoblast cells, and CD45 for immune cells. Expression of the VEGFRs and pSTAT3 were subsequently characterized by WMIF in conjunction with confocal microscopy. Results: A total of 18 PE and 18 NT placentas were evaluated. No significant differences in the cell type-specific expression patterns or expression levels of VEGFR1, VEGFR2 or VEGFR3 were detected between NT and PE placentas. In contrast, statistically significant increases in pSTAT3 staining were detected in endothelial cells of PE placentas versus NT controls. Discussion: Our study demonstrates that increased pSTAT3 expression in placental endothelial cells is associated with PE. We speculate that elevated pSTAT3 expression in the blood vessels of PE placentas may be due to aberrant angiogenesis, increased pro-inflammatory cytokine expression, and/or placental stress. Highlights: Normotensive versus preeclamptic placentas were compared by whole mount immunofluorescence. Expression levels and cellular distribution of the VEGFRs and pSTAT3 were examined. pSTAT3 expression was significantly higher in preeclamptic versus normotensive placentas.